Dicalcium phosphate and Vitamin A for calves on winter bluestem pasture, 1962-63 (Project 253-1) - Smith, E.F.; Richardson, D.; DeGeer, C.V.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The 40 steer calves, 10 per lot, used in this experiment were good-to-choice Herefords from near Fort Davis, Texas, assigned on a random-weight basis to their treatments. They were pastured together in a 190-acre bluestem pasture during the winter, penned three times weekly, divided into treatment groups and fed the experimental diets show in Table 40. The lots receiving dicalcium phosphate (0.1 pound per steer daily) and Vitamin A (10,000 I.U. daily) received it mixed with soybean meal.
Keywords: Beef; Dicalcium phosphate; Steers; Vitamin A; Bluestem pasture